O-79 Conducting an advance care planning randomised trial for incurable cancer patients: An australian experience. (1st September 2015) - Johnson, Stephanie
Abstract : Aim: To describe progress of a study that will evaluate in a randomised controlled trial the effect of a formal advance care planning intervention (ACP) on: The documentation and compliance with patients EOL wishes. The quality of death, costs of care and mental health outcomes of nominated family or friends will also be assessed. Method: 334 patients, who have incurable cancer with disease progression after 1st line chemotherapy and an expected survival of 3–12 months, as well as their nominated family or friend, will be randomised to receive usual care or usual care plus ACP. Result: ACP research can be challenging. 95 participant dyads (of 334) have been randomised to the study (data available for 89). Participants had a median age of 63 (M = 63.3, SD = 10), were married (70%) and non-tertiary educated (83%). The majority identified their ethnicity as Australian (72%). Mean oncologist estimated median survival was 7.7 months (SD = 2.9). Current progress on the study and challenges to implementation of the research and recruitment will be presented, as well as data regarding screening, inclusion and exclusion of participants. Conclusion: Barriers to the implementation of ACP research include: availability of skilled staff, standardisation of ACP interventions, cultural, administrative and technical barriers at hospital sites such as reluctance by clinical staff to introduce ACP research to patients and medical record systems which do not support ACP documentation. Barriers to recruitment include: patient refusal due to time barriers and fear of distress, carer refusal and low referral rate from oncologists.